PENGEMBANGAN MEDIA PEMBELAJARAN POWERPOINT PADA MATA KULIAH KONSEP DASAR IPA 2 UNTUK MENINGKATKAN HASIL BELAJAR MAHASISWA PROGRAM S-1 PGSD UNESA - Julianto, (Pendidikan Sekolah Dasar, 2010)
It has been developed instructional media by using the PowerPoint program on Konsep Dasar IPA  2. Development media is done by model 4-D (Four D Models) this is; define, design, development, and disseminate. This research was only carried out until the stage of development.  The study is targeted media a PowerPoint program on  light subpokok limited to 2 class E and H. The instrument used is a sheet of student questionnaire responses, and test results of student learning. Techniques of collecting data from this study is a student questionnaire and test results of student learning. From the percentage of responses will be obtained answers to the response criteria that will determine the feasibility of the media. Media is feasible if the percentage reaches â¥ 61%. Results of analysis of research data on the quality of the media display the percentage of answers obtained an average of 73.6%. Result analysis of the suitability of the media obtained an average percentage of responses of 89.6%. Results of student a learning obtained fairly good percentage with average 80%. Therefore, it can be concluded that media a PowerPoint learning fit for use as a medium of learning and can improve student learning outcomes